Therapy, Pain & Training - Jendrusch G; Henke T; Schnell D; Platen P (Dynamic Media Sales Verlag, 2022)
Problem: Visual deficits/ametropia are particularly significant obstacles in sports because the visual system controls/corrects all of an athletes movements. However, athletes are at increased risk for eye injuries caused by high-velocity objects e.g. balls or physical contact with opponents. This study presents the current (German) figures on eye injuries in club and school sports and evaluates the risk of eye injuries in various sports.Methods: We evaluated 2,392 eye injuries, selected from the 221,273 club sports injuries recorded in the Ruhr University Bochum and ARAG Sports Insurance database for the period 1987-2017. The school sports eye injuries recorded by the German Social Accident Insurance for 2019 were also analyzed.Results: Of all the club sports injuries recorded, 1.08% were eye injuries; of these, 19.7% had to be treated in hospital, 13.9% required surgery, and 56.9% prevented the injured athletes from working. Blunt trauma was the most common cause of injury, comprising more than 50% of cases. Eye injuries were strongly overrepresented in club sports injuries sustained during water polo, squash, badminton, and tennis (injury proportion ratio (IPR)=5.1-8.8). In school sports, eye injuries comprised 1.83% of the reported cases.Discussion: Eye injuries in sports are relatively rare, but often serious. Based on the increased IPR found for some sports, further studies must analyze the risk of eye injury in more detail. Eye protection in the form of sport-appropriate glasses should be used.Key Words: Sport Injury, Injury Proportion Ratio, Eye Protection, Sport Safety